International human rights, environment, and trade agreements implications of the anticipatory prohibition on the golden rice research: The imprudence of walking behind the BT eggplant trials ba - Tolentino, Armon Perez (Animo Repository, 2015)
The purpose of this research is to explain why it is judicially unwise to stop the Golden Rice research as the ban on Bt eggplant field trials is likely to set precedent, owing to its persuasive effect. The international legal implications of this prohibition will be shown through the legal basis of the rights to food and health, biosafety, and global free trade that are all interwoven in the case of the Golden Rice research. This research will allow the reader to weigh between the imaginative risks that are falsely protected through the precautionary principle and the scientifically supported benefits of the viability of Golden Rice as a food-base approach to blindness prevention and hunger alleviation — for the achievement of the constitutionally ordained rising standard of living, more specially for women and children — whose roles in nation building cannot be insolently ignored.